Neutrophils Play a Protective Nonphagocytic Role in Systemic Mycobacterium tuberculosis Infection of Mice - Pedrosa, Jorge (American Society for Microbiology, 2000)
Evidence showing that neutrophils play a protective role in the host response to infection by different intracellular parasites has been published in the past few years. We assessed this issue with regard to the infection of mice with Mycobacterium tuberculosis. We found a chronic recruitment of neutrophils to the infection foci, namely, to the peritoneal cavity after intraperitoneal infection and to the spleen and liver after intravenous inoculation of the mycobacteria. However, bacilli were never found associated with the recruited neutrophils but rather were found inside macrophages. The intravenous administration of the antineutrophil monoclonal antibody RB6-8C5 during the first week of infection led to selective and severe neutropenia associated with an enhancement of bacillary growth in the target organs of the mice infected by the intravenous route. The neutropenia-associated exacerbation of infection was most important in the liver, where a bacterial load 10-fold higher than that in nonneutropenic mice was found; the exacerbation in the liver occurred both during and after the neutropenic period. Early in infection by M. tuberculosis, neutropenic mice expressed lower levels of mRNAs for gamma interferon and inducible nitric oxide synthase in the liver compared to nondepleted mice. These results point to a protective role of neutrophils in the host defense mechanisms against M. tuberculosis, which occurs early in the infection and is not associated with the phagocytic activity of neutrophils but may be of an immunomodulatory nature.